2014
DOI: 10.1128/jvi.02151-14
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Dependent Membrane Fusion Induced by the gp41 Membrane-Proximal External Region–Transmembrane Domain Connection Suggests a Mechanism for Broad HIV-1 Neutralization

Abstract: The HIV-1 glycoprotein 41 promotes fusion of the viral membrane with that of the target cell. Structural, biochemical, and biophysical studies suggest that its membrane-proximal external region (MPER) may interact with the HIV-1 membrane and induce its disruption and/or deformation during the process. However, the high cholesterol content of the envelope (ca. 40 to 50 mol%) imparts high rigidity, thereby acting against lipid bilayer restructuring. Here, based on the outcome of vesicle stability assays, all-ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 75 publications
6
67
0
Order By: Relevance
“…However, the Env(671-704) sequence covering the entire gp41 TMD and a fraction of the adjacent MPER shows a high degree of conservation (18,26,36), consistent with the additional functional roles ascribed to this region during the infectious cycle, i.e. membrane fusion promotion (17,18,36) and immune response modulation (30 -32). Despite these important functional roles, high resolution structural data on the gp41 TMD and its junction to MPER were lacking ( Table 4).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…However, the Env(671-704) sequence covering the entire gp41 TMD and a fraction of the adjacent MPER shows a high degree of conservation (18,26,36), consistent with the additional functional roles ascribed to this region during the infectious cycle, i.e. membrane fusion promotion (17,18,36) and immune response modulation (30 -32). Despite these important functional roles, high resolution structural data on the gp41 TMD and its junction to MPER were lacking ( Table 4).…”
Section: Discussionsupporting
confidence: 55%
“…Although the molecular mechanism remains unsolved, MPER-N-TMD promotes membrane fusion as evidenced by mutagenesis studies and peptide-based assays (18,36,64,70). Consistent with a pivotal role in the fusion process, bNAbs raised .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, the membrane-proximal external region (MPER) and MSD of HIV-1 Env have been shown to be crucial for promoting fusogenicity. Disruption of hinge regions or the tryptophan-rich sequence in the MPER of HIV-1 Env, as well as polar residues within the MSD, all result in nonfunctional glycoproteins that are fusogenically inactive (24)(25)(26)(27)(28)(29). The potential role for the MSDs of MLV and HIV-1 Env in potentiating molecular rearrangements necessary for fusogenic activity would be analogous to the MSDs of voltage-gated ion channels and G-protein-coupled receptors (GPCRs).…”
mentioning
confidence: 99%
“…Even though glycoproteins are not observed to cluster in large preexisting domains in the absence of viral assembly, viral assembly could trigger the coalescence of smaller microdomains that contain the viral glycoproteins. It has been demonstrated that the cholesterol recognition amino acid consensus (CRAC) domain in the membrane-proximal external region (MPER) of HIV-1 Env has a propensity to interact with cholesterol-rich domains in the plasma membrane (25)(26)(27)(28)(29) and is necessary for remodeling of the HIV-1 lipid membrane to facilitate fusion (30)(31)(32). Additionally, the tryptophan-rich region immediately upstream of the HIV-1 Env CRAC domain has been implicated in HIV-1 Env acquisition into viral particles (30).…”
mentioning
confidence: 99%